Inventory approach for short-chain chlorinated paraffins for the Stockholm Convention implementation in Brazil. (January 2022) - Guida, Yago; Capella, Raquel; Kajiwara, Natsuko; Babayemi, Joshua Olajiire; Torres, João Paulo Machado; Weber, Roland
Abstract: Chlorinated paraffins (CPs) are chemicals with multipurpose applications. Their global production has increased despite their adverse impacts on the environment and human health. In 2017, short-chain chlorinated paraffins (SCCPs) were listed as persistent organic pollutants (POPs) in the Stockholm Convention. Yet, specific exemptions were granted for their applications despite the recycling prohibition for products containing SCCPs. Therefore, we aimed to produce the first Brazilian inventory of SCCPs following its respective guidance to evaluate the applicability of the SCCP inventory guidance and to provide technical insights regarding SCCPs in the update of the Brazilian National Implementation Plan (NIP). Moreover, we performed a review of SCCP occurrence in Brazil to fulfil data gaps in the inventory development. We identified and consulted nationwide stakeholders and assessed foreign trade data of CPs and products that might contain CPs in relevant amounts. The Brazilian production of CPs was discontinued in 1994. However, CPs are still imported and used in the country. CPs have been mostly applied as plasticizers, flame retardants and lubricants in Brazil. The import of products containing CPs also pose a significant route of CP entrance into Brazil. Thus, the current end-of-life management of CP-containing products is a bottleneck towards the Convention implementation. The guidance application was feasible and useful despite the low engagement of stakeholders. To assess foreign trade of CPs and CP-containing products, we recommend the use of more specific tracking codes. Besides, the review of SCCP occurrence is not a demanded part for an inventory but was a useful complementation. Graphical abstract: Image 1 Highlights: First national inventory of SCCPs for the Stockholm Convention implementation. The Brazilian production of chlorinated paraffins was discontinued in 1994. CPs are imported and mainly used as flame retardants, plasticizers and lubricants. Brazil imports high-volumes of PVC & rubber containing plasticizers, including CPs. Products containing CPs are not properly managed and disposed of in Brazil.